Students’ Mathematical Reasoning: A Systematic Literature Review with a Focus on Metaphorical Thinking-Based Learning Approaches - Annisa Desti Fahjri; Siti Fatimah; Jarnawi Afgani Dahlan (Universitas Lambung Mangkurat, 2026)
Mathematical reasoning is a fundamental component of meaningful mathematics learning; however, research on instructional approaches that systematically support its development remains fragmented. In particular, studies on mathematical reasoning and metaphorical thinking have largely evolved independently, resulting in limited integrative insights. Studies on mathematical reasoning and metaphorical thinking have often developed separately, resulting in limited understanding of how metaphorical-thinking-based learning contributes to reasoning development. This systematic literature review (SLR) aims to synthesize research trends on students’ mathematical reasoning in mathematics education and to examine how metaphorical-thinking-based learning approaches support the development of mathematical reasoning. Following the PRISMA 2020 framework, a systematic search of the Scopus and ERIC databases identified 36 peer-reviewed journal articles published between 2017 and 2025. The selected studies were analyzed using reflexive thematic analysis focusing on research trends, instructional implementations, metaphor types, learning models, and reported effects on students’ mathematical reasoning. The findings indicate that mathematical reasoning is increasingly viewed as a multidimensional construct involving cognitive, representational, social, and contextual aspects. The review also reveals that metaphorical thinking functions as a cognitive bridge that connects abstract mathematical concepts with students’ concrete experiences through conceptual, structural, orientational, cultural, and embodied metaphors. These metaphorical approaches are integrated into various instructional models, including Realistic Mathematics Education, ethnomathematics, problem-based learning, embodied learning, and technology-supported learning environments. Furthermore, the findings highlight several research gaps, including limited empirical studies explicitly linking metaphorical thinking and mathematical reasoning, insufficient longitudinal evidence, and limited comparative analysis across metaphor types. Overall, this review emphasizes the need for more theoretically integrated and empirically grounded studies on metaphor-based mathematical reasoning in mathematics education.